Using telehealth to support community health workers in Uganda during COVID-19: a mixed-method study - Maarten Olivier Kok; Tosca Terra; Raymond Tweheyo; Marinka van der Hoeven; Maiza Campos Ponce; Marceline Tutu van Furth; Elizeus Rutebemberwa (BMC, 2023)
Abstract Background At the onset of the COVID-19 pandemic, a local consortium in Uganda set up a telehealth approach that aimed to educate 3,500 Community Health Workers (CHW) in rural areas about COVID-19, help them identify, refer and care for potential COVID-19 cases, and support them in continuing their regular community health work. The aim of this study was to assess the functioning of the telehealth approach that was set up to support CHWs during the COVID-19 pandemic. Methods For this mixed-method study, we combined analysis of routine consultation data from the call-center, 24 interviews with key-informants and two surveys of 150 CHWs. Data were analyzed using constant comparative method of analysis. Results Between March 2020 and June 2021, a total of 35,553 consultations took place via the call center. While the CHWs made extensive use of the call center, they rarely asked for support for potential Covid-19 cases. According to the CHWs, there were no signs that people in their communities were suffering from severe health problems due to COVID-19. People compared the lack of visible symptoms to diseases such as Ebola and were skeptical about the danger of COVID-19. At the same time, people in rural areas were afraid to report relevant symptoms and get tested for fear of being quarantined and stigmatized. The telehealth approach did prove useful for other purposes, such as supporting CHWs with their regular tasks and coordinating the supply of essential products. The health professionals at the call center supported CHWs in diagnosing, referring and treating patients and adhering to infection prevention and control practices. The CHWs felt more informed and less isolated, saying the support from the call center helped them to provide better care and improved the supply of medicine and other essential health products. Conclusions The telehealth approach, launched at the start of the COVID-19 pandemic, provided useful support to thousands of CHWs in rural communities in Uganda. The telehealth approach could be quickly set up and scaled up and offers a low cost strategy for providing useful and flexible support to CHWs in rural communities.